Towards an enhanced understanding of aid policy reform: Learning from the French case. (22nd November 2018) - Cumming, Gordon D.
Summary: Major overhauls of aid policies and institutions are comparatively rare. When they happen, they are usually ascribed to pressures arising from outside donor agencies. Where internal forces for change are identified, the focus is on field operatives rather than political entrepreneurs based in donor head offices. This article homes in on the role of the political entrepreneur and shows how this actor can help effect top‐down reforms to overseas development assistance. It does so by combining a political entrepreneurship perspective with a broader theorisation of policy change, historical institutionalism, and applying this innovative framework to French aid reforms over the years (2001–2010) when Jean‐Michel Severino was Managing Director of the Agence Française de Développement. It finds that, although historical institutionalism can explain the broad direction of French changes in terms of "structural factors" such as exogenous shocks and new institutional configurations, it struggles to account for incremental shifts and the emergence of "new" ideas. Political entrepreneurship addresses these issues through its emphasis on individual human agents and their operational and ideational strategies. It concludes that this relatively parsimonious framework could provide an enhanced understanding of other reforms in the international development field and beyond.